Meta-analysis of the prevalence of restless leg syndrome and associated risk factors in chronic kidney disease patients - Aini, Nur; Janitra, Fitria Endah; Putri, Alfiani Rahmi; Fauk, Nelsensius Klau; Arifin, Hidayat (Universitas Airlangga, 2024)
Introduction: Restless legs syndrome (RLS) presents as a sleep-related issue in individuals with chronic kidney disease (CKD), contributing to heightened sleep disturbances and diminished quality of life. Consequently, this meta-analysis was conducted to assess the prevalence of RLS among CKD patients. Methods: A comprehensive search for articles published between inception and September 2023 was conducted across CINAHL, Cochrane, Embase, Ovid-MEDLINE, PubMed, Scopus, and Web of Science databases. A Comprehensive Meta-Analysis (CMA) software version 3.0 with random effects models was used for pooled prevalence and prediction interval analysis. Heterogeneity was assessed using the I2 test and Cochran's Q-statistic. The quality of the studies was evaluated using Hoy's risk of bias. Additionally, moderator analyses were performed to investigate variations in the prevalence estimates among the included studies. Results: A total of 97 studies were included in this meta-analysis with 315,875 participants. The pooled prevalence of RLS among CKD patients was 25% (95%CI: 20% to 32%). In terms of the demographic breakdown, the prevalence of RLS was nearly comparable in adults and children/adolescents at 25% and 21%, respectively. The prediction interval indicated a potential future RLS prevalence ranging from 1% to 88%. Notably, iron and phosphorus levels emerged as significant moderating factors influencing the prevalence of RLS. Conclusions: Roughly 25% of individuals with chronic kidney disease (CKD) encounter restless legs syndrome (RLS). It is imperative to foster collaboration among healthcare professionals to facilitate proactive management and early assessment of RLS, thereby enhancing the overall quality of life for CKD patients.